A method for preparing polyethylene furandicarboxylate fiber

By optimizing the melt blending wire process parameters of PEF fibers, improving the break strength and elongation of the break of the fibers, the problem of insufficient performance of the existing PEF fibers is solved, and the 100% bio-based characteristics of the material is maintained, achieving higher Mechanical performance and better environmental protection performance.

CN118895576BActive Publication Date: 2025-02-11SHANGHAI DEFULUN CHEM FIBER
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411375625.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-11
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing PEF fibers have low break strength and elongation of break, which is difficult to meet the needs of subsequent processing applications. The increased durability of microplastics of the copolymerized modified materials violates the original intention of bio-based polyester materials.

Method used

By optimizing melt blended spinning process parameters, including increasing screw speed and reducing spinning box temperature, enhancing melt flowability of polyethylene furandiformate, improving fiber orientation and crystallization performance, and passing through a ring with high pressure differential Blow-air cooling and multi-stage drafting process improve the break strength and elongation of the fibers.

Benefits of technology

It significantly improves the mechanical properties of polyethylene furandiformate fibers, with break strength and elongation of break reaching between 3.5-4.5cN/dtex and 40.1-55.5%, meeting the wider application needs while maintaining 100% Bio-based characteristics conform to the concept of green and sustainable development.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of bio-based fiber preparation and relates to a preparation method of polyethylene furandicarboxylate fiber. The polyethylene furandicarboxylate slices are dried and then melt-blended and spun. After drying, the polyethylene furandicarboxylate slices have a moisture content of ≤200ppm, a crystallinity of 30%-50%, and a softening temperature of 120-140°C. The melt-blended spinning comprises a screw extruder melt extrusion process, a spinning process, a ring-blowing cooling process, a two-stage drafting process and a tense heat setting process. The process parameters of the melt-blending spinning include: a screw speed of 28-35r / min, a spinning box temperature of 265-280°C, a pressure difference between an annular blowing air inlet and a return air of 600-800Pa, a primary drafting temperature of 70-80°C, a secondary drafting temperature of 100-120°C, a total drafting multiple of 2.94-3.52 times, and a tense heat setting temperature of 140-160°C. The polyethylene furandicarboxylate fiber of the invention has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bio-based fiber preparation and relates to a method for preparing polyethylene furandicarboxylate fiber. Background Art

[0002] Bio-based polyester materials are a class of materials with great development potential. The raw materials for their synthesis mainly come from renewable biomass resources, such as those obtained from crops, plants or other biological sources. These biomass resources are converted into polyester materials through a series of specific chemical processing processes. Unlike traditional fossil-based materials, the production process of bio-based polyester materials reduces dependence on non-renewable fossil energy. Moreover, after degradation, most of the products of bio-based polyester materials are environmentally friendly substances such as carbon dioxide and water, which put relatively little pressure on the environment. However, traditional bio-based polyester materials are mainly composed of aliphatic molecular chains. Because their molecular chains are highly flexible, there is no stable structure like the benzene ring in polyethylene terephthalate (PET) in the molecular chains, which makes it difficult for the material's breaking strength and elongation to be comparable to PET.

[0003] As a new type of bio-based polyester material, polyethylene furandicarboxylate (PEF) is the only material with a ring structure (rigid furan ring) among bio-based polyesters, which makes its breaking strength and breaking elongation better than traditional bio-based polyester materials. The uniqueness of PEF lies in the fact that furandicarboxylic acid (FDCA) in its molecular structure replaces PTA in PET. FDCA, as the main synthetic raw material of PEF, is the only bio-based platform compound with an aromatic ring structure. Its raw materials are mainly derived from carbohydrates such as glucose and fructose. It is a 100% bio-based material and is regarded as the most competitive green alternative to PTA. This key substitution not only changes the raw material source of PEF from relying on limited fossil resources to widely available and renewable carbohydrates (such as glucose, fructose, etc.), but also gives PEF excellent biodegradability.

[0004] PEF fibers synthesized by direct esterification or transesterification of FDCA with bio-based diols are known as the "next generation polyester" because of their similar structure and similar properties to PET, especially some better performance. They have huge market potential. However, in the PEF spinning process, since FDCA replaces PTA in PET, the regularity of the molecular chain decreases, which in turn affects the orientation and crystallization properties of the fiber, resulting in a decrease in the fiber's breaking strength and elongation at break, making it difficult to meet the needs of subsequent processing applications. For example, the document "Synthesis and Performance Research of Bio-based Polyethylene 2,5-Furandicarboxylate and Its Copolyesters 2019" used a single-screw extruder to explore PEF melt spinning and found that PEF monofilaments are brittle and difficult to stretch, and their breaking strength is only 1.15cN / dtex. For example, the document "Synthesis and fiber preparation of spinning-grade bio-based polyethylene furandicarboxylate [J]. Journal of Donghua University, 2023, 49 (3): 53-60" uses an insoluble catalyst and process conditions to synthesize PEF and prepare PEF fibers through a two-step spinning process. The maximum breaking strength of the prepared PEF fiber is only 2.17 cN / dtex. For another example, patent CN106544754B discloses a method for preparing 2,5-furandicarboxylic acid-based polyester fiber, which solid-phase thickens PEF and then blends it with a decarboxylation inhibitor and an antioxidant before spinning. The resulting fiber has a breaking strength of 4.5-4.7 cN / dtex, but due to the increase in the intrinsic viscosity after thickening, the fiber breaking elongation is only 25-30%.

[0005] In order to improve the breaking strength and elongation of PEF fibers, researchers have tried to copolymerize PEF, that is, to copolymerize PTA, FDCA and diols. However, good results have not been achieved. For example, the document "Study on Melt Spinnability and Fiber Structure and Properties of Polyethylene Terephthalate-2,5-Furandicarboxylate Copolyester (PEFT) [D], 2018" shows that after spinning and drawing, the breaking strength of the fiber is only 3.0 cN / dtex. For another example, patent CN117209735B extrudes the dried cationic dyeable bio-based furandicarboxylic acid polyester chips through screw extrusion, metering, cooling, bundling, hot drawing and winding. The breaking strength of the obtained fiber is only 3.4 cN / dtex at most, and the elongation at break is only 17%. In addition, after the copolymerization reaction, the copolymer still has benzene ring structural units provided by PTA. The benzene ring structure is more stable during the degradation process, which will lead to the problem of increased persistence of microplastics in the environment, thus violating the original intention of bio-based polyester materials.

[0006] Therefore, how to optimize the production process of PEF fiber through copolymerization modification or other technologies while maintaining the 100% bio-based characteristics of PEF materials to ensure that it has both high breaking strength and elongation at break and maintains environmental protection characteristics has become an important research direction in the current field of bio-based fiber preparation. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing polyethylene furandicarboxylate fiber.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing polyethylene furandicarboxylate fiber comprises drying polyethylene furandicarboxylate slices and then performing melt blending spinning. After drying, the polyethylene furandicarboxylate slices have a moisture content of ≤200 ppm, a crystallinity of 30%-50%, and a softening temperature of 120-140° C. If the moisture content of the polyethylene furandicarboxylate slices is high, the yarn will be broken, affecting the spinning quality. If the softening temperature and crystallinity of the polyethylene furandicarboxylate slices are low, a ring may occur in the screw, causing the spinning to be interrupted.

[0010] The melt blending spinning includes a screw extruder melt extrusion process, a spinning process, a ring blowing cooling process, a two-stage drawing process and a tense heat setting process;

[0011] The process parameters of melt blending spinning include: screw speed 28-35r / min, spinning box temperature 265-280℃, pressure difference between inlet and return air of 600-800Pa, primary drafting temperature 70-80℃, secondary drafting temperature 100-120℃, total drafting multiple 2.94-3.52 times, tensile heat setting temperature 140-160℃;

[0012] Compared with the prior art, the present invention adopts a higher screw speed and a lower spinning box temperature, which can enhance the melt fluidity of polyethylene furandicarboxylate. The better the melt fluidity, the more stable the filament discharge, and the more regular the arrangement of the molecular chains. Therefore, the orientation and crystallization of the fiber in the drawing and heat setting stages are better, which is manifested in the improvement of the breaking strength and the breaking elongation.

[0013] The present invention also adopts a relatively high pressure difference between the inlet and return air of the ring-blown air, so that the cooling of the fiber can be more uniform. After the fiber is uniformly cooled, the molecular chain can be built into the lattice faster, and the formed crystals are relatively small and more perfect. Therefore, in the drafting stage, the arrangement of the crystals and the amorphous regions (i.e., the non-crystalline regions) inside the molecular chain becomes more regular and orderly. This structural optimization directly leads to a significant improvement in the breaking strength and breaking elongation of the fiber.

[0014] At the same time, under specific drawing temperature and drawing multiple conditions, all fibers can reach a fully drawn state, at which time the fiber's breaking strength and breaking elongation both reach the optimal level; if the drawing is insufficient, the fiber's breaking strength will be relatively low, while the breaking elongation will be high; on the contrary, if the drawing is excessive, the fiber's breaking elongation will be significantly reduced;

[0015] In addition, the present invention maintains a relatively low tensile heat setting temperature, thereby ensuring a high stability of fiber molding, which in turn helps to improve the overall performance of the fiber; on the contrary, if the fiber molding stability is low, the fiber is prone to shrinkage during subsequent processing, which will lead to a decrease in the fiber's breaking strength.

[0016] As the preferred technical solution:

[0017] In the method for preparing polyethylene furandicarboxylate fiber as described above, before drying, the polyethylene furandicarboxylate chips have an intrinsic viscosity of 0.65-0.66 dL / g and a melting point of 215-217°C.

[0018] In the preparation method of polyethylene furandicarboxylate fiber as described above, drying is carried out by combining programmed temperature rise with programmed vacuum extraction. Through programmed temperature rise and programmed vacuum extraction, water molecules on the surface and inside of the slice can be extracted respectively. At the same time, during the heating process, the movement of the molecular chains is enhanced, the molecular chains in the amorphous region are further crystallized, the crystallinity of the slice is improved, and the molecular chains in the amorphous region are fewer. Therefore, in the initial stage of melting, the energy required for the movement of the molecular chains is higher, and the softening temperature of the slice is also higher.

[0019] The preparation method of polyethylene furandicarboxylate fiber as described above comprises the following drying process: first drying at 80-100°C for 2-3h, then heating to 90-120°C, evacuating to 0.2MPa and drying for 6-8h, and finally maintaining the temperature unchanged, continuing to evacuate to 0.05MPa and drying for 4-6h.

[0020] In the preparation method of polyethylene furandicarboxylate fiber as described above, the primary drawing adopts oil bath heating, and the primary drawing multiple is 2.8-3.2 times; the secondary drawing adopts steam heating, and the secondary drawing multiple is 1.05-1.1 times.

[0021] In the method for preparing polyethylene furandicarboxylate fiber as described above, the process parameters of melt blending spinning also include: screw temperature 250-280°C, pump supply 800-980g / min, and winding speed 1000-1150m / min.

[0022] In the method for preparing polyethylene furandicarboxylate fiber as described above, the melt blending spinning further comprises a relaxation and heat setting step.

[0023] The preparation method of polyethylene furandicarboxylate fiber as described above, the overall process flow of melt blending spinning is: screw extruder melt extrusion → spinning → cooling → winding → molding → bundling → drawing → tension heat setting → curling → oiling → relaxation heat setting.

[0024] The method for preparing polyethylene furandicarboxylate fiber as described above has a breaking strength of 3.5-4.5 cN / dtex, an elongation at break of 40.1-55.5%, an extra-long fiber content of 0-3 mg / 100 g, a defect content of 3-20 mg / 100 g, a curl number of 12-15 / 25 mm, a curl rate of 14%-18%, a linear density of 2.22-4.44 dtex, and a linear density deviation rate of -5%≤≤5%.

[0025] Beneficial effects:

[0026] (1) The present invention significantly improves the mechanical properties (breaking strength and breaking elongation) of polyethylene furandicarboxylate fibers by optimizing melt blending spinning process parameters, thereby meeting a wider range of application requirements.

[0027] (2) The present invention does not introduce any fossil-based raw materials, ensuring the 100% bio-based characteristics of the polyethylene furandicarboxylate fiber, which is in line with the concept of green and sustainable development.

[0028] (3) Poly(ethylene furandicarboxylate) fiber is completely derived from renewable biomass resources. Its degradation products are mainly carbon dioxide and water, which is environmentally friendly and reduces the risk of microplastic pollution. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0030] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0031] Moisture content: Tested in accordance with GB / T 14190-2017 "Test method for fiber-grade polyester (PET) chips" standard;

[0032] Crystallinity: Tested in accordance with GB / T 19466.3-2004 standard;

[0033] Softening temperature: Tested in accordance with GB / T 1633-2000 standard;

[0034] Intrinsic viscosity: tested in accordance with GB / T 14190-2017 standard;

[0035] Melting point: Tested in accordance with GB / T 14190-2017 standard;

[0036] Linear density and extra-long fiber content: measured in accordance with GB / T 14335-2008 standard;

[0037] Breaking strength and breaking elongation: measured in accordance with GB / T 14337-2022, where the tensile speed is 30 mm / min;

[0038] Defect content: measured in accordance with GB / T 14339-2008 standard;

[0039] Curl number and curl rate: measured in accordance with GB / T 14338-2022 standard.

[0040] Example 1

[0041] A method for preparing polyethylene furandicarboxylate fiber, the specific steps are as follows:

[0042] (1) Preparation of raw materials;

[0043] Polyethylene furandicarboxylate chips: intrinsic viscosity is 0.65 dL / g, melting point is 215°C;

[0044] (2) Drying the polyethylene furandicarboxylate slices, the drying process is as follows: first drying at 80°C for 2 hours, then heating to 116°C, evacuating to 0.2 MPa and drying for 8 hours, and finally maintaining the temperature unchanged, evacuating to 0.05 MPa and drying for 6 hours;

[0045] The moisture content of the dried polyethylene furandicarboxylate slices was 100 ppm, the crystallinity was 40.3%, and the softening temperature was 125.2°C;

[0046] (3) the dried polyethylene furandicarboxylate slices are sequentially subjected to melt extrusion, spinning, cooling, winding, forming, bundling, primary drawing (using oil bath heating), secondary drawing (using steam heating), tension heat setting, curling, oiling, and relaxation heat setting to obtain polyethylene furandicarboxylate fibers;

[0047] Among them, the relevant process parameters are: screw zone 1 temperature 250℃, screw zone 2 temperature 255℃, screw zone 3 temperature 260℃, screw zone 4 temperature 265℃, screw zone 5 temperature 260℃, screw zone 6 temperature 255℃, screw speed 31r / min, pump supply 890g / min, spinning box temperature 265℃, pressure difference between inlet and return air of ring blowing 720Pa, winding speed 1050m / min, primary stretching temperature 72℃, primary stretching multiple 3.1 times, secondary stretching temperature 110℃, secondary stretching multiple 1.05 times, tension heat setting temperature 155℃.

[0048] The final polyethylene furandicarboxylate fiber has a linear density of 3.33 dtex, a linear density deviation rate of 0.1%, a breaking strength of 4.5 cN / dtex, an elongation at break of 48.9%, an extra-long fiber content of 0.5 mg / 100 g, a defect content of 3 mg / 100 g, a curl number of 14.5 / 25 mm, and a curl rate of 16.4%.

[0049] Comparative Example 1

[0050] A method for preparing a fiber is basically the same as that in Example 1, except that: the drying process is: first drying at 80°C for 2 hours, then heating to 90°C, evacuating to 0.2MPa and drying for 4 hours, and finally keeping the temperature unchanged, continuing to evacuate to 0.05MPa and drying for 2 hours; the moisture content of the polyethylene furandicarboxylate slices after drying is 210ppm, the crystallinity is 38.5%, and the softening temperature is 118°C.

[0051] During the melt blending spinning process, the fibers frequently drifted and broke, and the pressure of the spinning assembly was low. The final fiber had a breaking strength of 3.3 cN / dtex and an elongation at break of 35.4%.

[0052] Compared with Example 1, the breaking strength and breaking elongation of the fiber of Comparative Example 1 are significantly reduced. This is because the moisture content of the polyethylene furandicarboxylate chips used in the spinning of Comparative Example 1 is too high, resulting in broken fibers and affecting the spinning quality.

[0053] Comparative Example 2

[0054] A method for preparing a fiber is basically the same as that in Example 1, except that: the drying process is: first drying at 80°C for 2 hours, then heating to 110°C, evacuating to 0.2MPa and drying for 6 hours, and finally keeping the temperature unchanged, continuing to evacuate to 0.05MPa and drying for 4 hours; the moisture content of the dried polyethylene furandicarboxylate slices is 100ppm, the crystallinity is 25% and the softening temperature is 110°C.

[0055] Since the softening temperature and crystallinity of the polyethylene furandicarboxylate chips are too low, a ring knot appears in the screw during spinning and spinning cannot continue.

[0056] Comparative Example 3

[0057] A method for preparing fiber is basically the same as that in Example 1, except that the screw speed is 25 r / min.

[0058] The final fiber had a breaking strength of 3.5 cN / dtex and a breaking elongation of 34.7%.

[0059] Comparative Example 4

[0060] A method for preparing a fiber is basically the same as that in Example 1, except that the spinning box temperature is 285°C.

[0061] The final fiber had a breaking strength of 3.4 cN / dtex and a breaking elongation of 32.9%.

[0062] Compared with Example 1, the breaking strength and elongation of the fibers in Comparative Examples 3 and 4 are significantly reduced. This is because the lower screw speed and the higher spinning box temperature reduce the melt fluidity of polyethylene furandicarboxylate, resulting in poor melt fluidity, unstable filament production, and irregular arrangement of molecular chains. Therefore, the orientation and crystallization of the fibers in the stretching and heat setting stages are deteriorated, which is manifested as a decrease in breaking strength and elongation.

[0063] Comparative Example 5

[0064] A method for preparing fiber is basically the same as that in Example 1, except that the pressure difference between the inlet and return air of the annular blowing air is 580Pa.

[0065] The final fiber had a breaking strength of 3.2 cN / dtex and a breaking elongation of 30.7%.

[0066] Compared with Example 1, the breaking strength and breaking elongation of the fiber in Comparative Example 5 are significantly reduced. This is because the lower pressure difference between the annular air inlet and return air makes the cooling of the fiber uneven. The uneven cooling of the fiber prevents the molecular chains from being built into the crystal lattice faster, and the formed crystals are relatively large and imperfect. Therefore, in the stretching stage, the arrangement of the crystals and the amorphous regions (i.e., the non-crystalline regions) inside the molecular chains becomes less regular and orderly. This structural degradation directly leads to a significant reduction in the breaking strength and breaking elongation of the fiber.

[0067] Comparative Example 6

[0068] A method for preparing a fiber is basically the same as that in Example 1, except that the primary drafting multiple is 2.6 times, the secondary drafting multiple is 0.9 times, and the total drafting multiple is 2.34 times.

[0069] The final fiber had a breaking strength of 3.4 cN / dtex and a breaking elongation of 57.3%.

[0070] Compared with Example 1, the breaking strength of the fiber in Comparative Example 6 is significantly reduced, and the breaking elongation is significantly increased. This is because insufficient drawing leads to the existence of uncrystallized amorphous regions inside the fiber. The molecular chains in the amorphous regions are relatively elastic and can be further drawn, resulting in an increase in the breaking elongation. At the same time, the decrease in crystallinity causes a decrease in breaking strength.

[0071] Comparative Example 7

[0072] A method for preparing a fiber is basically the same as that in Example 1, except that the primary drafting multiple is 3.25 times, the secondary drafting multiple is 1.1 times, and the total drafting multiple is 3.58 times.

[0073] The elongation at break of the final fiber was 39.7%.

[0074] Compared with Example 1, the elongation at break of Comparative Example 7 is significantly reduced. This is because excessive stretching leads to excessive crystallinity inside the fiber and a lower content of amorphous molecular chains. During the stretching process, there are fewer molecular chains that can move freely, which is manifested as a decrease in the elongation at break of the fiber.

[0075] Comparative Example 8

[0076] A method for preparing a fiber is basically the same as that of Example 1, except that the tensile heat setting temperature is 170°C.

[0077] The breaking strength of the finally prepared fiber is 3.4 cN / dtex.

[0078] Compared with Example 1, the breaking strength of the fiber in Comparative Example 8 is significantly reduced. This is because the higher tensile heat setting temperature reduces the stability of fiber molding, and the fiber is prone to shrinkage during subsequent processing, resulting in a decrease in the breaking strength of the fiber.

[0079] Example 2

[0080] A method for preparing polyethylene furandicarboxylate fiber is basically the same as that in Example 1, except that the intrinsic viscosity of the polyethylene furandicarboxylate chips is 0.66 dL / g and the melting point is 217°C; the moisture content of the polyethylene furandicarboxylate chips after drying is 100 ppm, the crystallinity is 40.8%, and the softening temperature is 125.7°C.

[0081] The final polyethylene furandicarboxylate fiber has a linear density of 3.21 dtex, a linear density deviation rate of -0.5%, a breaking strength of 4.3 cN / dtex, an elongation at break of 48.2%, an extra-long fiber content of 0.7 mg / 100 g, a defect content of 3.2 mg / 100 g, a curl number of 14.3 / 25 mm, and a curl rate of 15.7%.

[0082] Example 3

[0083] A method for preparing polyethylene furandicarboxylate fiber is basically the same as that in Example 1, except that the winding speed is 1100 m / min.

[0084] The final polyethylene furandicarboxylate fiber has a linear density of 3.26 dtex, a linear density deviation rate of 0.3%, a breaking strength of 4.3 cN / dtex, an elongation at break of 48.3%, an extra-long fiber content of 1 mg / 100 g, a defect content of 3 mg / 100 g, a curl number of 13.9 / 25 mm, and a curl rate of 14.5%.

[0085] Example 4

[0086] A method for preparing polyethylene furandicarboxylate fiber is basically the same as that in Example 1, except that the screw speed is 33 r / min and the pump supply is 940 g / min.

[0087] The final polyethylene furandicarboxylate fiber has a linear density of 3.84 dtex, a linear density deviation rate of -0.3%, a breaking strength of 4 cN / dtex, an elongation at break of 40.2%, an extra-long fiber content of 1.4 mg / 100 g, a defect content of 4 mg / 100 g, a curl number of 12.5 / 25 mm, and a curl rate of 17.1%.

[0088] Example 5

[0089] A method for preparing polyethylene furandicarboxylate fiber is basically the same as Example 1, except that: the temperature of screw zone 1 is 255°C, the temperature of screw zone 2 is 260°C, the temperature of screw zone 3 is 265°C, the temperature of screw zone 4 is 270°C, the temperature of screw zone 5 is 265°C, the temperature of screw zone 6 is 260°C, the screw speed is 30r / min, the spinning box temperature is 270°C, the winding speed is 1100m / min, the secondary drafting multiple is 1.08 times, and the tension heat setting temperature is 160°C.

[0090] The final polyethylene furandicarboxylate fiber has a linear density of 3.17 dtex, a linear density deviation rate of -1%, a breaking strength of 3.9 cN / dtex, an elongation at break of 49.4%, an extra-long fiber content of 0.6 mg / 100 g, a defect content of 3.2 mg / 100 g, a curl number of 13.9 / 25 mm, and a curl rate of 17.3%.

[0091] Example 6

[0092] A method for preparing polyethylene furandicarboxylate fiber is basically the same as Example 1, except that: the temperature of screw zone 1 is 260°C, the temperature of screw zone 2 is 265°C, the temperature of screw zone 3 is 270°C, the temperature of screw zone 4 is 275°C, the temperature of screw zone 5 is 270°C, the temperature of screw zone 6 is 265°C, the screw speed is 29r / min, the spinning box temperature is 275°C, the winding speed is 1100m / min, and the primary drafting multiple is 3 times.

[0093] The final polyethylene furandicarboxylate fiber has a linear density of 3.1 dtex, a linear density deviation of 0.8%, a breaking strength of 3.7 cN / dtex, an elongation at break of 50.1%, an extra-long fiber content of 0.6 mg / 100 g, a defect content of 3.2 mg / 100 g, a curl number of 14.6 / 25 mm, and a curl rate of 17.6%.

[0094] Example 7

[0095] A method for preparing polyethylene furandicarboxylate fiber is basically the same as that in Example 2, except that the pressure difference between the annular blowing inlet and return air is 740 Pa.

[0096] The final polyethylene furandicarboxylate fiber has a linear density of 3.41 dtex, a linear density deviation of 1%, a breaking strength of 4.4 cN / dtex, an elongation at break of 42.6%, an extra-long fiber content of 0 mg / 100 g, a defect content of 3.5 mg / 100 g, a curl number of 12.7 / 25 mm, and a curl rate of 14.3%.

[0097] Example 8

[0098] A method for preparing polyethylene furandicarboxylate fiber is basically the same as that of Example 2, except that the tensile heat setting temperature is 155°C.

[0099] The final polyethylene furandicarboxylate fiber has a linear density of 3.4 dtex, a linear density deviation of 0.7%, a breaking strength of 4.1 cN / dtex, an elongation at break of 41.5%, an extra-long fiber content of 1.2 mg / 100 g, a defect content of 3.5 mg / 100 g, a curl number of 12 / 25 mm, and a curl rate of 14%.

[0100] Example 9

[0101] A method for preparing polyethylene furandicarboxylate fiber is basically the same as Example 2, except that the screw speed is 35 r / min and the pump supply is 980 g / min.

[0102] The final polyethylene furandicarboxylate fiber has a linear density of 3.44 dtex, a linear density deviation rate of 0.5%, a breaking strength of 4 cN / dtex, an elongation at break of 45.2%, an extra-long fiber content of 2 mg / 100 g, a defect content of 4.3 mg / 100 g, a curl number of 13.4 / 25 mm, and a curl rate of 16.8%.

[0103] Example 10

[0104] A method for preparing polyethylene furandicarboxylate fiber is basically the same as Example 2, except that: the temperature of screw zone 1 is 265°C, the temperature of screw zone 2 is 270°C, the temperature of screw zone 3 is 275°C, the temperature of screw zone 4 is 280°C, the temperature of screw zone 5 is 275°C, the temperature of screw zone 6 is 270°C, the screw speed is 28r / min, the spinning box temperature is 280°C, the winding speed is 1100m / min, the primary drafting multiple is 3.2 times, the secondary drafting multiple is 1.1 times, and the tensile heat setting temperature is 155°C.

[0105] The final polyethylene furandicarboxylate fiber has a linear density of 2.22 dtex, a linear density deviation of 0.7%, a breaking strength of 3.5 cN / dtex, an elongation at break of 55.5%, an extra-long fiber content of 0.4 mg / 100 g, a defect content of 3.3 mg / 100 g, a curl number of 15 / 25 mm, and a curl rate of 18%.

[0106] Embodiment 11

[0107] A method for preparing polyethylene furandicarboxylate fiber, the specific steps are as follows:

[0108] (1) Preparation of raw materials;

[0109] Polyethylene furandicarboxylate chips: intrinsic viscosity is 0.65 dL / g, melting point is 215°C;

[0110] (2) Drying the polyethylene furandicarboxylate slices, the drying process is as follows: first drying at 100°C for 2 hours, then heating to 90°C, evacuating to 0.2 MPa and drying for 6 hours, and finally maintaining the temperature unchanged, continuing to evacuate to 0.05 MPa and drying for 4 hours;

[0111] The moisture content of the dried polyethylene furandicarboxylate slices was 200 ppm, the crystallinity was 50.0%, and the softening temperature was 120.0°C;

[0112] (3) the dried polyethylene furandicarboxylate slices are sequentially subjected to melt extrusion, spinning, cooling, winding, forming, bundling, primary drawing (using oil bath heating), secondary drawing (using steam heating), tension heat setting, curling, oiling, and relaxation heat setting to obtain polyethylene furandicarboxylate fibers;

[0113] Among them, the relevant process parameters are: screw zone 1 temperature 250℃, screw zone 2 temperature 255℃, screw zone 3 temperature 260℃, screw zone 4 temperature 265℃, screw zone 5 temperature 260℃, screw zone 6 temperature 255℃, screw speed 31r / min, pump supply 800g / min, spinning box temperature 265℃, pressure difference between inlet and return air of ring blowing 600Pa, winding speed 1000m / min, primary stretching temperature 70℃, primary stretching multiple 3.1 times, secondary stretching temperature 100℃, secondary stretching multiple 1 times, tension heat setting temperature 160℃.

[0114] The final polyethylene furandicarboxylate fiber has a linear density of 3.22 dtex, a linear density deviation rate of -0.3%, a breaking strength of 3.6 cN / dtex, an elongation at break of 46.4%, an extra-long fiber content of 1.5 mg / 100 g, a defect content of 20 mg / 100 g, a curl number of 13.6 / 25 mm, and a curl rate of 14.8%.

[0115] Example 12

[0116] A method for preparing polyethylene furandicarboxylate fiber, the specific steps are as follows:

[0117] (1) Preparation of raw materials;

[0118] Polyethylene furandicarboxylate chips: intrinsic viscosity is 0.66dL / g, melting point is 217℃;

[0119] (2) Drying the polyethylene furandicarboxylate slices, the drying process is as follows: first drying at 80°C for 3 hours, then heating to 120°C, evacuating to 0.2 MPa and drying for 8 hours, and finally maintaining the temperature unchanged, evacuating to 0.05 MPa and drying for 6 hours;

[0120] The moisture content of the dried polyethylene furandicarboxylate slices was 80 ppm, the crystallinity was 30.0%, and the softening temperature was 140.0°C;

[0121] (3) the dried polyethylene furandicarboxylate slices are sequentially subjected to melt extrusion, spinning, cooling, winding, forming, bundling, primary drawing (using oil bath heating), secondary drawing (using steam heating), tension heat setting, curling, oiling, and relaxation heat setting to obtain polyethylene furandicarboxylate fibers;

[0122] Among them, the relevant process parameters are: screw zone 1 temperature 250℃, screw zone 2 temperature 255℃, screw zone 3 temperature 260℃, screw zone 4 temperature 265℃, screw zone 5 temperature 260℃, screw zone 6 temperature 255℃, screw speed 31r / min, pump supply 890g / min, spinning box temperature 265℃, pressure difference between inlet and return air of ring blowing 800Pa, winding speed 1150m / min, primary stretching temperature 80℃, primary stretching multiple 3.1 times, secondary stretching temperature 120℃, secondary stretching multiple 1.1 times, tension heat setting temperature 155℃.

[0123] The final polyethylene furandicarboxylate fiber has a linear density of 2.88 dtex, a linear density deviation rate of 0.5%, a breaking strength of 4 cN / dtex, an elongation at break of 49.5%, an extra-long fiber content of 3 mg / 100 g, a defect content of 10 mg / 100 g, a curl number of 14 / 25 mm, and a curl rate of 17.1%.

[0124] Embodiment 13

[0125] A method for preparing polyethylene furandicarboxylate fiber, the specific steps are as follows:

[0126] (1) Preparation of raw materials;

[0127] Polyethylene furandicarboxylate chips: intrinsic viscosity is 0.66dL / g, melting point is 217℃;

[0128] (2) Drying the polyethylene furandicarboxylate slices, the drying process is as follows: first drying at 80°C for 2 hours, then heating to 116°C, evacuating to 0.2 MPa and drying for 8 hours, and finally maintaining the temperature unchanged, evacuating to 0.05 MPa and drying for 6 hours;

[0129] The moisture content of the dried polyethylene furandicarboxylate slices was 95 ppm, the crystallinity was 40.9%, and the softening temperature was 125.8°C;

[0130] (3) the dried polyethylene furandicarboxylate slices are sequentially subjected to melt extrusion, spinning, cooling, winding, forming, bundling, primary drawing (using oil bath heating), secondary drawing (using steam heating), tension heat setting, curling, oiling, and relaxation heat setting to obtain polyethylene furandicarboxylate fibers;

[0131] Among them, the relevant process parameters are: screw zone 1 temperature 250℃, screw zone 2 temperature 255℃, screw zone 3 temperature 260℃, screw zone 4 temperature 265℃, screw zone 5 temperature 260℃, screw zone 6 temperature 255℃, screw speed 31r / min, pump supply 890g / min, spinning box temperature 265℃, pressure difference between inlet and return air of ring blowing 720Pa, winding speed 1100m / min, primary stretching temperature 72℃, primary stretching multiple 2.8 times, secondary stretching temperature 100℃, secondary stretching multiple 1.05 times, tension heat setting temperature 140℃.

[0132] The final polyethylene furandicarboxylate fiber has a linear density of 4.44 dtex, a linear density deviation rate of -5%, a breaking strength of 3.8 cN / dtex, an elongation at break of 41.4%, an extra-long fiber content of 1.6 mg / 100 g, a defect content of 6 mg / 100 g, a curl number of 14.1 / 25 mm, and a curl rate of 16.8%.

[0133] Embodiment 14

[0134] A method for preparing polyethylene furandicarboxylate fiber, the specific steps are as follows:

[0135] (1) Preparation of raw materials;

[0136] Polyethylene furandicarboxylate chips: intrinsic viscosity is 0.66dL / g, melting point is 217℃;

[0137] (2) Drying the polyethylene furandicarboxylate slices, the drying process is as follows: first drying at 80°C for 2 hours, then heating to 116°C, evacuating to 0.2 MPa and drying for 8 hours, and finally maintaining the temperature unchanged, evacuating to 0.05 MPa and drying for 6 hours;

[0138] The moisture content of the dried polyethylene furandicarboxylate slices was 95 ppm, the crystallinity was 40.8%, and the softening temperature was 125.7°C;

[0139] (3) the dried polyethylene furandicarboxylate slices are sequentially subjected to melt extrusion, spinning, cooling, winding, forming, bundling, primary drawing (using oil bath heating), secondary drawing (using steam heating), tension heat setting, curling, oiling, and relaxation heat setting to obtain polyethylene furandicarboxylate fibers;

[0140] Among them, the relevant process parameters are: screw zone 1 temperature 250℃, screw zone 2 temperature 255℃, screw zone 3 temperature 260℃, screw zone 4 temperature 265℃, screw zone 5 temperature 260℃, screw zone 6 temperature 255℃, screw speed 31r / min, pump supply 890g / min, spinning box temperature 265℃, pressure difference between inlet and return air of ring blowing 720Pa, winding speed 1100m / min, primary stretching temperature 72℃, primary stretching multiple 2.9 times, secondary stretching temperature 110℃, secondary stretching multiple 1.08 times, tension heat setting temperature 145℃.

[0141] The final polyethylene furandicarboxylate fiber has a linear density of 3.98 dtex, a linear density deviation of 5%, a breaking strength of 3.5 cN / dtex, an elongation at break of 40.1%, an extra-long fiber content of 0.8 mg / 100 g, a defect content of 7 mg / 100 g, a curl number of 12.9 / 25 mm, and a curl rate of 17.3%.

Claims

1. A method for preparing polyethylene furandicarboxylate fiber, comprising: drying polyethylene furandicarboxylate slices and then melt-blending and spinning, characterized in that: After drying, the moisture content of the polyethylene furandicarboxylate slices is ≤200ppm, the crystallinity is 30%-50%, and the softening temperature is 120-140°C; The melt blending spinning includes a screw extruder melt extrusion process, a spinning process, a ring blowing cooling process, a two-stage drawing process and a tense heat setting process; The process parameters of melt blending spinning include: screw speed 28-35r / min, spinning box temperature 265-280℃, pressure difference between inlet and return air of 600-800Pa, primary drafting temperature 70-80℃, primary drafting multiple 2.8-3.2 times, secondary drafting temperature 100-120℃, secondary drafting multiple 1.05-1.1 times, total drafting multiple 2.94-3.52 times, tensile heat setting temperature 140-160℃; The breaking strength of the polyethylene furandicarboxylate fiber is 3.5-4.5 cN / dtex, and the breaking elongation is 40.1-55.5%.

2. The method for preparing polyethylene furandicarboxylate fiber according to claim 1, characterized in that: Before drying, the intrinsic viscosity of the polyethylene furandicarboxylate chips is 0.65-0.66 dL / g and the melting point is 215-217°C.

3. The method for preparing polyethylene furandicarboxylate fiber according to claim 1, characterized in that: Drying is carried out by combining programmed temperature rise with programmed vacuum extraction.

4. The method for preparing polyethylene furandicarboxylate fiber according to claim 3, characterized in that: The drying process is as follows: first, dry at 80-100°C for 2-3h, then heat to 90-120°C, evacuate to 0.2MPa and dry for 6-8h, and finally keep the temperature unchanged, continue to evacuate to 0.05MPa and dry for 4-6h.

5. The method for preparing polyethylene furandicarboxylate fiber according to claim 1, characterized in that: The first stage drafting adopts oil bath heating; the second stage drafting adopts steam heating.

6. The method for preparing polyethylene furandicarboxylate fiber according to claim 5, characterized in that: The process parameters of melt blending spinning also include: screw temperature 250-280°C, pump supply 800-980g / min, and winding speed 1000-1150m / min.

7. The method for preparing polyethylene furandicarboxylate fiber according to claim 1, characterized in that: The melt blend spinning also includes a relaxation and heat setting process.

8. The method for preparing polyethylene furandicarboxylate fiber according to claim 7, characterized in that: The overall process flow of melt blending spinning is: screw extruder melt extrusion → spinning → cooling → winding → molding → bundling → drawing → tension heat setting → curling → oiling → relaxation heat setting.

9. The method for preparing polyethylene furandicarboxylate fiber according to any one of claims 1 to 8, characterized in that: The ultra-long fiber content of polyethylene furandicarboxylate fiber is 0-3 mg / 100 g, the defect content is 3-20 mg / 100 g, the crimp number is 12-15 / 25 mm, the crimp rate is 14%-18%, the linear density is 2.22-4.44 dtex, and the linear density deviation rate is -5%≤≤5%.

Citation Information

Patent Citations

  • Preparation method of 2,5-furandicarboxylic acid-based polyester fiber

    CN106544754B

  • Process for the preparation of a fiber, a fiber and a yarn made from such a fiber

    US20160138193A1